2016
DOI: 10.18632/oncotarget.12755
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of synergy: An investigation of the PI3K/mTOR/MEK co-targeted inhibition strategy in NSCLC

Abstract: Clinical PI3K inhibition has been somewhat disappointing, due to both inadequate patient stratification and compensatory cell signalling through bypass mechanisms. As such, investigation of PI3K-MEK co-targeted inhibition has been recommended. With high mortality rates and a clear need for new therapeutic intervention strategies, non-small cell lung cancer (NSCLC) is an important setting to investigate the effectiveness of this approach.Here, 174 NSCLC tumours were screened for 150 mutations by Fluidigm techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In fact, this cell line began to exhibit decreased sensitivity to the drug after just one month, and developed a log fold difference in IC50 concentration between parent (H1975GP) and resistant (H1975GR) cell lines after just 4 months of treatment with Apitolisib (GDC-0980). H1975 cells were shown to harbour mutations in both PIK3CA and PIK3R1 , and have previously been shown to express PI3K pathway signalling phosphoproteins more highly than the other cell lines used here 32 .…”
Section: Discussionmentioning
confidence: 82%
“…In fact, this cell line began to exhibit decreased sensitivity to the drug after just one month, and developed a log fold difference in IC50 concentration between parent (H1975GP) and resistant (H1975GR) cell lines after just 4 months of treatment with Apitolisib (GDC-0980). H1975 cells were shown to harbour mutations in both PIK3CA and PIK3R1 , and have previously been shown to express PI3K pathway signalling phosphoproteins more highly than the other cell lines used here 32 .…”
Section: Discussionmentioning
confidence: 82%
“…However, recently a growing body of evidence has shown that it could do more in NSCLC and TKI resistance especially take PTEN/PI3K/AKT pathway into consideration [ 16 ]. Since clinical PI3K inhibition has been somewhat disappointing, people are now trying to co-inhibit PI3K with other factors at the same time to achieve a better outcome [ 17 , 18 ]. MMP9 is closely associated with cancer, due to its role in extracellular matrix remodeling and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…66 However, many have exhibited issues with toxicity or resistance due to compensatory mechanisms and feedback loops with closely related signaling pathways, and co-targeted inhibition approaches have been gaining popularity in preclinical studies. [67][68][69][70] Thus, PIM and PI3K co-targeting may be a viable approach owing to the overlap between those pathways, the proven PIMinduced resistance to PI3K inhibition 35 and the reported successful synergism that results when both are used. 71 Synergy between inhibitors could allow the use of lower therapeutic doses to achieve the same clinical effect, thus potentially reducing treatment toxicity and improving patient quality of life.…”
Section: Pim Inhibition Within the Prostate Cancer Clinical Pathwaymentioning
confidence: 99%